How are women faring in the Bangladeshi labour market? Evidence from labour force survey data - Bidisha, Sayema Haque; Faruk, Avinno; Mahmood, Tanveer (Sage Journals, 2024)
This article was published in The South Asia Economic Journal [©2022 Rights managed by Sage Journals] and the definite version is available at: https://doi.org/10.1177/13915614221108564 The Article's website is at: https://journals.sagepub.com/doi/10.1177/13915614221108564